ANALISIS PERKEMBANGAN UMKM DI LINGKUNGAN UNIVERSITAS JAMBI KAMPUS PINANG MASAK TERHADAP PENDAPATAN MASYARAKAT DALAM PERSPEKTIF ISLAM - Ary Dean Amri; Meilin Haziah; Fery Adriansyah; Avia Salsabillah; Ika Nur Aini; Jevy Rahmand; Ilham Bagus Kurniawan; Nur Fitria Syawaliyah Hasfiyani (Nusantara Hasana Journal, 2023)
This study aims to analyze the development of micro, small and medium enterprises within the University of Jambi. This research method uses a qualitative descriptive method. The technique used in sampling was the questionnaire method which was given to 30 respondents. The results of this study indicate the level of influence on interest in entrepreneurship within the University of Jambi is indicated by the highest percentage of 97%. While the influence on motivation criteria, income level, operating profit and business prospects is shown with the highest percentage of 63%. Then the influence on the criteria for business turnover and business potential is shown with the highest percentage of 57%. While the influence on the development of micro, small and medium enterprises within the University of Jambi on the level of the total workforce is 47%. By using a Likert scale calculation that is calculated from all respondents' answers, it is known that on average all respondents answered strongly agree with a percentage of 91% and the rest stated that they strongly disagree with a percentage of 8%. So that the existence of Jambi University is very influential on the development of micro, small and medium enterprises in their environment.